Non-canonical Mechanisms of Presynaptic Kainate Receptors Controlling Glutamate Release - Negrete-Díaz, José V.; Sihra, Talvinder S.; Flores, Gonzalo; Rodríguez-Moreno, Antonio (Frontiers in Molecular Neuroscience, 2018)
A metabotropic modus operandi for kainate receptors (KARs) was first discovered in 1998 modulating GABA release. These receptors have been also found to modulate glutamate release at different synapses in several brain regions. Mechanistically, a general biphasic mechanism for modulating glutamate release by presynaptic KARs with metabotropic actions has emerged, with low KA concentrations invoking an increase in glutamate release, whereas higher concentrations of KA mediate a decrease in the release of this neurotransmitter. The molecular mechanisms underpinning the opposite modulation of glutamate release are distinct, with a G-protein-independent, adenylate cyclase- and protein kinase A-dependent mechanism mediating the facilitation of glutamate release, while a G-protein dependent mechanism (with or without protein kinase recruitment) is involved in the decrease of neurotransmitter release. In the present review, we revisit the mechanisms underlying the non-canonical modus operandi of KARs effecting the bimodal control of glutamatergic transmission different brain regions, and address the possible functions that this modulation may support.